2017
DOI: 10.18632/oncotarget.19354
|View full text |Cite
|
Sign up to set email alerts
|

Local blockage of self-sustainable erythropoietin signaling suppresses tumor progression in non-small cell lung cancer

Abstract: Functional significance of co-expressed erythropoietin (EPO) and its receptor (EPOR) in non-small cell lung cancer (NSCLC) had been under debate. In this study, co-overexpression of EPO/EPOR was confirmed to be positively associated with poor survival in NSCLC. The serum EPO in 14 of 35 enrolled NSCLC patients were found elevated significantly and decreased to normal level after tumor resection. With primary tumor cell culture and patient-derived tumor xenograft (PDX) mouse model, the EPO secretion from the tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 38 publications
1
9
0
Order By: Relevance
“…6a, b and Additional file 2: Table S4, SP1 was upregulated whereas EGR1 was downregulated in the NSCLC specimens as compared with the normal lung tissues. We also found that phosphor-EPO-R (pEPO-R) and HIF1α were also significantly higher in NSCLC, which is consistently with our previous report [17]. The expression levels of pEPO-R, HIF1α and SP1 were positively while EGR1 was negatively associated in NSCLC (Fig.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…6a, b and Additional file 2: Table S4, SP1 was upregulated whereas EGR1 was downregulated in the NSCLC specimens as compared with the normal lung tissues. We also found that phosphor-EPO-R (pEPO-R) and HIF1α were also significantly higher in NSCLC, which is consistently with our previous report [17]. The expression levels of pEPO-R, HIF1α and SP1 were positively while EGR1 was negatively associated in NSCLC (Fig.…”
Section: Resultssupporting
confidence: 91%
“…On the other hand, no significant EPO-R expression was detected in several systematic screenings in both tumor cell lines and solid tumor specimens [21, 22]. In NSCLC, we previously identified high- and low-EPO-R cell population and we found that tumor-derived EPO significantly stimulated the growth of EPO-R-positive NSCLC cells [17]. Here in this study, we further confirmed that EPO-R expression was inducible under hypoxia (independent of basal expression level) in NSCLC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the one hand, high EPOR expression in locally advanced squamous cell carcinoma of the head and neck was considered to be an independent prognostic factor for OS and was associated with poorer OS [35], and activation of EPOR in melanoma was thought to promote tumor progression and contributed to survival of tumor cells [52], meanwhile, inhibition of EPOR gene expression in NSCLC reduced the growth of NSCLC cells under hypoxia [53]; on the one hand, there was no signi cant difference in survival rates between patients with different EPOR expression in gastric and cervical adenocarcinoma [28,36]; on the other hand, recurrence-free survival was signi cantly improved in ER+/EPOR+ breast cancer patients with untreated tamoxifen in breast cancer [54], and in the breast cancer cell lines, RAMA 37 cells (low EPOR expression) had a stronger proliferation ability than RAMA 37-28 cells (high EPOR expression), suggesting that high EPOR expression can reduce the ability of cells to divide [55], in addition, high levels of EPOR mRNA in myeloma were associated with better survival [37]. In some data, EPO/EPOR co-expression or co-overexpression in NSCLC was associated with poor prognosis [38][39][40], but independent evidence on the prognostic impact of EPOR on patients was lacking.…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, high EPOR expression in locally advanced squamous cell carcinoma of the head and neck was considered to be an independent prognostic factor for OS and was associated with poorer OS [35], and activation of EPOR in melanoma was thought to promote tumor progression and contributed to survival of tumor cells [52], meanwhile, inhibition of EPOR gene expression in NSCLC reduced the growth of NSCLC cells under hypoxia [53]; on the one hand, there was no signi cant difference in survival rates between patients with different EPOR expression in gastric and cervical adenocarcinoma [28,36]; on the other hand, recurrence-free survival was signi cantly improved in ER+/EPOR+ breast cancer patients with untreated tamoxifen in breast cancer [54], and in the breast cancer cell lines, RAMA 37 cells (low EPOR expression) had a stronger proliferation ability than RAMA 37-28 cells (high EPOR expression), suggesting that high EPOR expression can reduce the ability of cells to divide [55], in addition, high levels of EPOR mRNA in myeloma were associated with better survival [37]. In some data, EPO/EPOR co-expression or co-overexpression in NSCLC was associated with poor prognosis [38][39][40], but independent evidence on the prognostic impact of EPOR on patients was lacking. Our results…”
Section: Discussionmentioning
confidence: 99%